Drivers of social media use amongSMEs and its impact onbrand awareness and customer engagement - Alkhasoneh O.M.; Jamaludin H.; Bin Zahar A.R.; Al-Sharafi M.A. (Emerald Publishing, 2025)
Purpose: Despite the widespread use of social media globally, SMEs exhibit a below-average adoption rate. This raises critical questions about the reasons behind SMEs' limited engagement with this ubiquitous platform. The primary objective of this research is to explore the factors influencing the utilization of social media by small and medium-sized enterprises (SMEs) and assess its influence on brand awareness and customer engagement in the Jordanian context. Design/methodology/approach: This study utilizes a quantitative research approach to examine SMEs' adoption of social media. Data are collected from 290 SMEs in Jordan through paper-based and online surveys employing purposive sampling. The validity of the proposed model is confirmed using a partial least squares (PLS) approach, specifically employing SmartPLS 4 for analysis. Findings: The results reveal that the examined model successfully captures the dynamics of social media usage among SMEs, shedding light on the significant drivers influencing their decision to use social media in their activities. The findings also underscore the pivotal role of social media usage in SMEs, particularly in enhancing brand awareness and fostering customer engagement within the Jordanian business landscape. Originality/value: This study significantly contributes to the existing literature by highlighting the practical implications of social media activity, specifically in the context of SMEs. Using the UTAUT2 model to examine the drivers of social media use among SMEs and extend it to assess the broader impact of social media usage on brand awareness and customer engagement adds uniqueness to the study, providing a more nuanced view of social media usage in the SME sector. ? 2024, Emerald Publishing Limited.